2007
DOI: 10.1097/01.anes.0000267601.09764.e6
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of α1GT-type Calcium Channels in Mice Does Not Change Anesthetic Requirements for Loss of the Righting Reflex and Minimum Alveolar Concentration but Delays the Onset of Anesthetic Induction

Abstract: The 50% effective concentration for loss of righting reflex and MAC values for the volatile anesthetics were not altered after alpha1G calcium channel knockout, indicating that normal functioning of alpha1G calcium channels is not required for the maintenance of anesthetic hypnosis and immobility. However, the timely induction of anesthesia/hypnosis by volatile anesthetic agents and some intravenous anesthetic agents may require the normal functioning of these channel subunits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
6
37
1
Order By: Relevance
“…or ethanol (3.5 g/kg) administration (Table 1). Though findings appeared to be in conflict with previous results showing no significant changes of LORR following the use of several general anesthetics (32), this discrepancy is most probably due to the difference of exposure or anesthetics dosages used to induce LORR. Although the 50% effective concentration for LORR in Ca V 3.1 KO mice was not altered, the latencies to develop LORR of Ca V 3.1 KO mice after exposure to anesthetics, such as isoflurane, halothane, sevoflurane, and pentobarbital, were longer (32), which our results have confirmed.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…or ethanol (3.5 g/kg) administration (Table 1). Though findings appeared to be in conflict with previous results showing no significant changes of LORR following the use of several general anesthetics (32), this discrepancy is most probably due to the difference of exposure or anesthetics dosages used to induce LORR. Although the 50% effective concentration for LORR in Ca V 3.1 KO mice was not altered, the latencies to develop LORR of Ca V 3.1 KO mice after exposure to anesthetics, such as isoflurane, halothane, sevoflurane, and pentobarbital, were longer (32), which our results have confirmed.…”
Section: Discussioncontrasting
confidence: 97%
“…Ca V 3.1 null KO mice and their littermate controls (WT) were generated by mating heterozygotes of Ca V 3.1 (C57BL/6) from RIKEN BioResource Center (32). Mice were housed with free access to food and water under controlled temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of the Ca V 3.1 gene did not result in detectable morphological abnormalities (27,28). KO mice did not display abnormal behavior in confined laboratory conditions: a 55-h activity survey did not indicate alteration of the global circadian activity (Fig.…”
Section: T-type Channel Blockade Prevents Ltp Induction With No Effecmentioning
confidence: 93%
“…Mice lacking the cacna1g gene (encoding Ca V 3.1) were produced as previously described (28). (21) was made up as a 10 mM stock solution in dimethyl sulfoxide (DMSO); aliquots were kept at -20°C and diluted for use as indicated at 1 μM concentrations known to block T-type calcium channels (21,23).…”
Section: Methodsmentioning
confidence: 99%
“…Modulation of GABA A receptors in this manner is known to be an important part of the mechanism of action for many anesthetics. More recent studies, however, have shown that general anesthetics can influence a number of voltage and ligand-gated ion channels (Campagna et al 2003;Chen et al 2007;Hemmings et al 2005;Krasowski and Harrison 1999;Petrenko et al 2007).…”
Section: Introductionmentioning
confidence: 99%